Energy limit of oil-immersed transformers: A concept and its application in different climate conditions; IET Generation, Transmission & Distribution; Vol. 15, iss. 3 - Daminov I. B. Ildar Bolatovich; Prokhorov A. V. Anton Viktorovich; Caire R. Raphael; Alvarez-Herault M.-C. Marie-Cecile (2021, 2021)
Title screen